An investigation of tourism information on destination management organization websites as the pull factor: A case study of health and wellness tourism information - Arunotai Pongwat (2018)
© 2017 IEEE. The current study investigates tourism information provided on the tourism destination management organization websites parallel with senior tourists' preferences, constraints, and travel behaviors to find the associations between them. As the exploratory study, the phenomenon within Thailand setting was solely explored. Senior travelers were mainly the samples of the research. Health and wellness tourism information provided on Tourism Authority of Thailand (TAT) websites were captured and analyzed based on the suggested tourism motivations. Netnography content analysis was employed to extract the data collected from senior travelers who participated in online travel communities. Three stages were conducted in the methodology, including examining the data captured from reviews available on the online travel community, TripAdvisor.com; exploring health and wellness information available on TAT websites; and analyzing and comparing the findings. The findings from TripAdvisor.com exposed that escapism motivation was the main motive that pushes senior travelers to visit Thailand. However, even though Thailand has been ranked among the world's top wellness destinations, health and wellness tourism was rarely mentioned in Thailand Travel Forum. The key constraints concerned weather issues, physical impairments, and accessibilities. By investigating TAT websites, more information about health and medical products and services were found, while information regarding wellness tourism product was absent. Since TAT and the government intended to attract more wellness senior tourists, both parties should deliver additional relevant and useful information essential for their trip planning and improve the functionality of the existing websites to enhance user experiences on the websites and communication competencies.